P85 Hiv-related Acute Respiratory Admissions – Good Outcomes And An Opportunity For Testing. (10th November 2014) - Howlett, P; Lux, D; Kulasegaram, R; Breen, RAM
Abstract : Introduction: The burden, changing pattern and outcome of HIV-associated lung disease following the introduction of anti-retroviral therapy (ART) remains to be defined. We sought to investigate these factors in an unselected cohort of individuals admitted acutely to our London teaching hospital. Methods: Consecutive admissions were prospectively collected between June 2013 and May 2014. In those where the cause for admission was an acute respiratory illness, patient notes and electronic records were interrogated. Patients were allowed >1 diagnoses and in-hospital outcomes only were reported. Results: Fifty-three of 149 (35%) acute HIV admissions were with respiratory causes, (3 patients had 2 admissions >30 days apart). Median age was 45 years and 28% (15) were female. Median CD4 count was 109 (range 3–867) cells/uL; 14 (26%) had fully suppressed HIV loads (VL <20 copies/ml). 4 of 53 (8%) were admitted with non-infectious diagnoses: 2 with lung cancer, 1 non-infective COPD exacerbation and 1 non-specific interstitial pneumonia. The remainder had infections: 12 (23%) had culture-confirmed bacterial pneumonia, 11 (21%) were treated for PCP, 8 (15%) had culture-confirmed Mycobacterium tuberculosis (1 MDR), 4 had confirmed viral pneumonia (8%). 20 (38%) patients completed treatment for pneumonia with no specific laboratory confirmation. The most common bacterial isolates were streptococcus pneumoniae (4 cases), haemophilus influenzae (3), pseudomonas aureginosa (2) and klebsiella pneumoniae (2). In 11 of 53 (22%) a new diagnosis of HIV was made at the time of admission, 10 of whom presented as acute community acquired pneumonia (CAP). In 9 of 11 (82%) CD4 count was <200 cells/uL and 6 of 11 (55%) required ICU care. In total 20 of 53 (38%) were admitted to ICU, and 8 (15%) required mechanical ventilation. Median length of stay in hospital was 9 (2–397) days. 1 of 53 (2%) patients died. Conclusions: Acute respiratory illness remains a significant cause of HIV admissions, with opportunistic and non-opportunistic pathogens commonly identified. Outcomes were reassuringly good despite the frequent need for ICU support. We believe our data underlines the important opportunity that a presentation with acute respiratory illness provides to test for and diagnose HIV infection.